Demi Bela Generasi Pendidikan Harus Siap Dihujat - Dahru Latif; Faisal Efendi; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to present it with critical reading. Descriptive qualitative research methods were used in the analysis. The results of the study show that it provides valuable insight into the importance of small habits in achieving significant changes in life, describes clearly and in detail the mechanisms of habit formation and strategies that can be applied to form successful habits and highlights the role of the environment in forming habits, providing practical guidance about how to create a generation that supports positive habit change.